Exposure to type 2 diabetes provokes mitochondrial impairment in apparently healthy human hearts - Zweck, Elric; Scheiber, Daniel; Jelenik, Tomas; Bönner, Florian; Horn, Patrick; Pesta, Dominik; Schultheiss, Heinz-Peter; Boeken, Udo; Akhyari, Payam; Lichtenberg, Artur; Kelm, Malte; Roden, Michael; et al. (Diabetes care, 2021)
Cardiac mitochondrial alterations are suspected to play a key role in the development of diabetes-related heart failure as reported in some animal and few human studies in type 2 diabetes (1). It is yet unclear whether these alterations are induced by diabetes-related metabolic changes or develop secondary to other factors underlying heart failure including micro- and macrovascular disease. We hypothesized that 1) exposure to type 2 diabetes provokes myocardial mitochondrial impairment prior to apparent left ventricular heart failure in humans and 2) these mitochondrial alterations are accompanied by increased oxidative stress, edema, and intracellular inflammation.